Catalyst for hydrogen production electrolysis of proton exchange membrane and preparation method of catalyst

Through the solvent thermal reduction method and the addition of an appropriate amount of potassium iodide, the scale and crystallinity of the iridium ruthenium alloy catalyst were improved, the problem of insufficient electrocatalytic activity and stability was solved, and the efficient hydrogen production electrolytic performance of proton exchange membrane was achieved.

CN119710791AActive Publication Date: 2025-03-28NINGBO DIGITAL TWIN (EASTERN UNIV OF TECH) RES INST +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411848308.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-28
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing iridium ruthenium alloy catalysts have problems of low electrocatalytic activity and poor stability in the hydrogen electrolysis of proton exchange membranes.

Method used

The solvent thermal reduction method is used, the triblock copolymer P123 is used as the reducing agent and protecting agent, ethanol is used as the solvent, and an appropriate amount of potassium iodide is added to improve the scale and crystallinity of the catalyst, thereby improving its electrocatalytic activity and stability.

Benefits of technology

The iridium ruthenium alloy catalyst prepared by this method has high catalytic activity and excellent stability. It is suitable for hydrogen electrolysis of proton exchange membranes and exhibits excellent redox (OER) electrocatalytic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710791A_ABST
    Figure CN119710791A_ABST
Patent Text Reader

Abstract

The invention discloses a proton exchange membrane hydrogen production electrolysis catalyst and a preparation method thereof.The preparation method comprises the following steps that S1, iridium precursor salt and ruthenium precursor salt are dissolved in water, and a solution A is obtained; s2, a triblock copolymer P123 is dissolved in ethyl alcohol, and a solution B is obtained; s3, dissolving potassium iodide in water to obtain a solution C; s4, uniformly mixing the solution A, the solution B and the solution C, transferring into a reaction kettle, and heating for reaction; and S5, collecting the product obtained in the step S4, and centrifuging and washing to obtain the iridium ruthenium alloy catalyst. According to the invention, a solvothermal reduction method is adopted, a triblock copolymer P123 is taken as a reducing agent and a protective agent, ethanol is taken as a solvent, and potassium iodide is added to improve the size and crystallization degree of the catalyst, so that the iridium-ruthenium alloy catalyst with high catalytic activity and high stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic technology, and in particular to a catalyst for proton exchange membrane hydrogen electrolysis and a preparation method thereof. Background Art

[0002] Proton exchange membrane (PEM) water electrolysis is an efficient and green hydrogen production technology with the advantages of high energy conversion efficiency, rapid response and small footprint. Its working principle is that water molecules are decomposed into oxygen and hydrogen ions under the action of anode catalysts, and hydrogen ions move to the cathode through the proton exchange membrane and generate hydrogen under the action of cathode catalysts.

[0003] Precious metal iridium (Ir) and ruthenium (Ru)-based materials are commonly used PEM electrolysis water hydrogen production anode electrocatalysts, and alloy catalysts can enhance catalytic activity by utilizing the synergistic effect between metals. The existing technology synthesizes iridium-ruthenium alloy catalysts by hydrothermal method, and the obtained alloy catalysts are mostly amorphous nanoparticles with a particle size of about 2nm and low overall structural crystallinity. In addition, catalysts with this morphology generally have low electrocatalytic activity and poor stability. Summary of the invention

[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to improve the electrocatalytic activity and stability of the iridium-ruthenium alloy catalyst.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a catalyst for proton exchange membrane hydrogen electrolysis, comprising the following steps: S1. dissolving an iridium precursor salt and a ruthenium precursor salt in water to obtain a solution A; S2, dissolving the triblock copolymer P123 in ethanol to obtain solution B; S3, dissolving potassium iodide in water to obtain solution C; S4, mixing the solution A, solution B and solution C uniformly, transferring the mixture to a reaction kettle, and heating the mixture for reaction; S5. Collect the product obtained in step S4, and obtain an iridium-ruthenium alloy catalyst by centrifugation and washing.

[0006] The invention adopts a solvent thermal reduction method, uses triblock copolymer P123 as a reducing agent and a protecting agent, uses ethanol as a solvent, and adds potassium iodide to increase the catalyst size and crystallinity, thereby obtaining an iridium-ruthenium alloy catalyst with high catalytic activity and high stability.

[0007] Furthermore, in step S4, in the mixed solution of solution A, solution B and solution C, the ratio of the total amount of the iridium precursor salt and the ruthenium precursor salt to the amount of potassium iodide is 1:0.1-3. The addition of an appropriate amount of potassium iodide can adjust the structure and surface composition of the iridium-ruthenium alloy system catalyst, so that the iridium and ruthenium with poor crystallinity originally become alloys with higher crystallinity and exposed high-index crystal faces.

[0008] Furthermore, in the step S4, in the mixed solution of solution A, solution B and solution C, the ratio of the total amount of the iridium precursor salt and the ruthenium precursor salt to the amount of the triblock copolymer P123 is 1:2-10.

[0009] Furthermore, in step S3, the mass concentration of potassium iodide in solution C is 0.04-0.4 g / mL.

[0010] Furthermore, in step S1, the mass concentration of the iridium precursor salt in the solution A is 0.001-0.005 g / mL, and the mass concentration of the ruthenium precursor salt is 0.001-0.003 g / mL.

[0011] Furthermore, in step S1, the iridium precursor salt is selected from one or a combination of two or more of iridium trichloride, iridium tetrachloride, chloroiridic acid, iridium acetate, ammonium chloroiridate and potassium hexachloroiridate; the ruthenium precursor salt is selected from one or a combination of two or more of ruthenium trichloride, ruthenium tetrachloride, ruthenium acetylacetonate and ammonium hexachlororuthenate.

[0012] Furthermore, in the step S2, the concentration of the triblock copolymer P123 in the solution B is 0.1-1.0 mol / L.

[0013] Furthermore, in step S4, the reaction temperature is 100-240° C., and the reaction time is 4-24 hours.

[0014] The second aspect of the present invention provides a catalyst for proton exchange membrane hydrogen electrolysis, which is prepared by the above preparation method. The catalyst synthesized by the present invention has excellent electrocatalytic OER performance and has good application and development prospects in PEM electrolyzers.

[0015] Furthermore, the catalyst is a core-shell structured nanoparticle with a size of 100 to 600 nm, and the catalyst of this morphology has excellent stability.

[0016] In summary, compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts a solvothermal method to prepare an iridium-ruthenium alloy catalyst, which can effectively improve the reduction efficiency and degree of difficult-to-reduce metal precursors compared to a hydrothermal method.

[0017] (2) The present invention adds KI halogen small molecules to the catalyst synthesis system, which can significantly improve the crystallinity of the synthesized IrRu nanoparticles. Depending on the amount of addition, they can self-assemble into large-scale yolk core-shell structures and show excellent stability.

[0018] (3) The present invention adds KI halogen molecules so that the iodide ions in the solvent regulate the formation of high-index crystal faces during the growth of nanoparticles, thereby further improving the catalytic activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a TEM image of the iridium-ruthenium alloy catalyst of Example 1 of the present invention.

[0020] Figure 2 It is a TEM image of the iridium-ruthenium alloy catalyst of Comparative Example 1 of the present invention.

[0021] Figure 3 1 is the XRD diagram of the iridium-ruthenium alloy catalyst of Example 1 of the present invention and Comparative Example 1.

[0022] Figure 4 1 is the LSV curve of the catalysts of the examples of the present invention and the comparative examples in 0.5M H2SO4.

[0023] Figure 5 It is a comparison chart of the stability test of the catalysts of the examples of the present invention and the comparative examples. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0025] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0027] The specific embodiment of the present invention provides a catalyst for proton exchange membrane hydrogen electrolysis and a preparation method thereof, wherein a solvent thermal reduction method is adopted, triblock copolymer P123 is used as a reducing agent and a protective agent, and ethanol is used as a solvent to prepare an iridium ruthenium alloy catalyst; and potassium iodide is added to control the catalyst size and crystallinity. The preparation method specifically comprises the following steps: S1. Dissolve a certain amount of iridium precursor salt and ruthenium precursor salt in water, and ultrasonicate until completely dissolved to obtain a dark reddish brown solution A. In a specific embodiment, the mass concentration of the iridium precursor salt in solution A is 0.001-0.005 g / mL, and the mass concentration of the ruthenium precursor salt is 0.001-0.003 g / mL. The iridium precursor salt can be selected from iridium trichloride, iridium tetrachloride, chloroiridic acid, iridium acetate, ammonium chloroiridate, potassium hexachloroiridate, etc., and the ruthenium precursor salt can be selected from ruthenium trichloride, ruthenium tetrachloride, ruthenium acetylacetonate, ammonium hexachlororuthenate, etc.

[0028] S2. Dissolve a certain amount of triblock copolymer P123 in ethanol, and perform ultrasonic treatment until the triblock copolymer P123 is completely dissolved to obtain a colorless transparent solution B. In a specific embodiment, the concentration of the triblock copolymer P123 in solution B is 0.1-1.0 mol / L.

[0029] S3. Dissolve a certain amount of potassium iodide in water, and perform ultrasonic treatment until it is completely dissolved to obtain a colorless transparent solution C. In a specific embodiment, the mass concentration of potassium iodide in solution C is 0.04-0.4 g / mL.

[0030] S4, after mixing solution A, solution B and solution C evenly, transfer them to a reactor and heat them for reaction, the reaction conditions are: reaction temperature 100-240°C, reaction time 4-24h. In a specific embodiment, the ratio of the total amount of the iridium precursor salt and the ruthenium precursor salt, the amount of the triblock copolymer P123 and the amount of potassium iodide in the mixed solution is controlled to be 1:2-10:0.1-3.

[0031] S5. Collect the product obtained in step S4, and obtain an iridium-ruthenium alloy catalyst by centrifugation and washing.

[0032] The above preparation method adds an appropriate amount of KI to the reaction prompt, which can adjust the structure and surface composition of the IrRu system catalyst, so that the originally poorly crystallinity Ir and Ru are transformed into alloys with higher crystallinity and higher exposed static crystal surface activity, thereby improving the catalytic activity; and the catalyst is more likely to self-assemble into a large-scale yolk core-shell structure, thereby improving stability.

[0033] In a specific embodiment, the nanoparticle size of the iridium-ruthenium alloy catalyst reaches 100-600 nm, and exposes a high-index {200} crystal face. The iridium-ruthenium alloy catalyst has excellent electrocatalytic OER performance and has good application and development prospects in PEM electrolyzers.

[0034] The technical effects of the present invention are described below in conjunction with specific embodiments. Unless otherwise specified, the raw materials in the embodiments of the present application are purchased through commercial channels. Example

[0035] The iridium-ruthenium alloy catalyst is prepared as follows: (1) Dissolve 0.0090 g IrCl3 and 0.0062 g RuCl3 in 600 μL deionized water and stir under ultrasonic to obtain solution A.

[0036] (2) Add 1.003 g of P123 into 60 mL of ethanol and stir ultrasonically to completely dissolve it to obtain solution B.

[0037] (3) Dissolve 0.08 g KI in 1 mL deionized water and stir under ultrasonication to obtain solution C.

[0038] (4) Mix solutions A, B and C evenly and transfer them to a hydrothermal reactor for reaction at 180°C for 12 h.

[0039] (5) The product is centrifuged and washed to obtain an iridium-ruthenium alloy catalyst, labeled as IrRu-KI. Example

[0040] The iridium-ruthenium alloy catalyst is prepared as follows: (1) Dissolve 0.010 g (NH4)2IrCl6 and 0.008 g RuCl4 in 600 μL deionized water and stir under ultrasonic to obtain solution A.

[0041] (2) Add 1 g of P123 into 60 mL of ethanol and stir ultrasonically to completely dissolve it to obtain solution B.

[0042] (3) Dissolve 0.1 g KI in 1 mL deionized water and stir under ultrasonication to obtain solution C.

[0043] (4) Solutions A, B and C were mixed evenly and transferred to a hydrothermal reactor for reaction at 150°C for 16 h.

[0044] (5) The product is centrifuged and washed to obtain an iridium-ruthenium alloy catalyst.

[0045] Comparative Example 1 The iridium-ruthenium alloy catalyst is prepared as follows: (1) Dissolve 0.0090 g IrCl3 and 0.0062 g RuCl3 in 600 μL deionized water and stir under ultrasonic to obtain solution A.

[0046] (2) Add 1.003 g of P123 into 60 mL of ethanol and stir ultrasonically to completely dissolve it to obtain solution B.

[0047] (3) After mixing solutions A and B evenly, transfer them to a hydrothermal reactor and react at 180°C for 12 h.

[0048] (5) The product is centrifuged and washed to obtain an iridium-ruthenium alloy catalyst, labeled as IrRu.

[0049] The TEM images of the iridium-ruthenium alloy catalysts prepared in Example 1 and Comparative Example 1 are as follows: Figure 1 and Figure 2 As shown by Figure 2 (a) It can be seen that the amorphous agglomerates of IrRu catalysts are composed of some small-scale particles, and there are obvious interfaces between the small particles; Figure 2 (b) It can be seen that the size of the catalyst particles is about 2nm; Figure 2 (c) It can be seen that the exposed crystal plane of the alloy is {111}. Figure 1 (a) It can be seen that the IrRu-KI catalyst prepared in Example 1 forms a larger-scale yolk core-shell structure, with a scale of about 300-400 nm; Figure 1 (b) shows that compared with Figure 2 (b) The small particles show that the catalyst nanoparticles have a higher degree of crystallization and more obvious lattice fringes. Figure 1 As can be seen in (c), the lattice fringes in the IrRu-KI catalyst appear as {200} crystal planes, indicating that the prepared iridium-ruthenium alloy has high-index crystal planes exposed.

[0050] The XRD patterns of the iridium-ruthenium alloy catalysts prepared in Example 1 and Comparative Example 1 are as follows: Figure 3 As shown, it shows that the IrRu catalyst forms an alloy with Ir face-centered cubic (fcc) structure. Since Ir is the main structure, it conforms to the standard PDF card. Compared with the IrRu catalyst, the IrRu-KI catalyst begins to show obvious diffraction peaks of the {200} crystal plane in the XRD diffraction characterization, which further confirms that the IrRu alloy regulated by KI has a high-index {200} crystal plane.

[0051] Comparative Example 2 Commercial RuO2 catalyst.

[0052] Experimental Example 1 A three-electrode system was constructed: the IrRu-KI catalyst prepared in Example 1, the IrRu catalyst prepared in Comparative Example 1, and the commercial RuO2 catalyst prepared in Comparative Example 2 were used as working electrodes, respectively; a platinum sheet was used as the counter electrode; a silver-silver chloride electrode was used as the reference electrode; a 0.5 M H2SO4 solution was used as the electrolyte; and the cathode cell and the anode cell were separated by an ion exchange membrane.

[0053] The LSV curve was obtained using the linear scanning method of the electrochemical workstation. The test results are shown in Figure 4 As shown in the figure, it can be seen that the catalytic activity of IrRu catalyst is significantly improved compared with commercial RuO2, while IrRu-KI catalyst further improves the OER catalytic activity. -2 At the current density of , the respective transition points are IrRu-KI (190mV), IrRu (228mV) and RuO2 (270mV).

[0054] Experimental Example 2 The stability tests were conducted on the IrRu-KI catalyst prepared in Example 1, the IrRu catalyst prepared in Comparative Example 1, and the commercial RuO2 catalyst prepared in Comparative Example 2. The results are as follows: Figure 5 As shown in the figure, it can be seen that the commercial RuO2 catalyst -2 The OER test at the current density was deactivated in less than 20 hours and the potential rose sharply. The performance of the IrRu catalyst was relatively stable, but at about 280 hours of testing, the overpotential of the catalyst exceeded 330mV. During the 500h test, the performance of IrRu-KI remained stable at an overpotential of 280mV without significant increase.

[0055] The above experimental results show that without adding KI, due to Ir 3+ It is difficult to reduce, the reduction rate is slow, and both Ir and Ru metals tend to form nanoparticles of about 2nm with exposed crystal faces based on {111} crystal faces, and then agglomerate to form an amorphous structure. - The ions can be selectively adsorbed on the {200} crystal plane of the IrRu alloy, resulting in the iodine ions causing the IrRu alloy to more selectively expose the {200} crystal plane. The resulting IrRu-KI alloy structure has a higher degree of crystallization and is easier to self-assemble into a yolk core-shell structure, thereby improving stability.

[0056] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for proton exchange membrane hydrogen electrolysis, characterized in that: The following steps are involved: S1. dissolving an iridium precursor salt and a ruthenium precursor salt in water to obtain a solution A; S2, dissolving the triblock copolymer P123 in ethanol to obtain solution B; S3, dissolving potassium iodide in water to obtain solution C; S4, mixing the solution A, solution B and solution C uniformly, transferring the mixture to a reaction kettle, and heating the mixture for reaction; S5. Collect the product obtained in step S4, and obtain an iridium-ruthenium alloy catalyst by centrifugation and washing.

2. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to claim 1, characterized in that: In the step S4, in the mixed solution of solution A, solution B and solution C, the ratio of the total amount of the iridium precursor salt and the ruthenium precursor salt to the amount of potassium iodide is 1:0.1-3.

3. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to claim 2, characterized in that: In the step S4, in the mixed solution of solution A, solution B and solution C, the ratio of the total amount of the iridium precursor salt and the ruthenium precursor salt to the amount of the triblock copolymer P123 is 1:2-10.

4. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to any one of claims 1 to 3, characterized in that: In step S3, the mass concentration of potassium iodide in solution C is 0.04-0.4 g / mL.

5. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to any one of claims 1 to 3, characterized in that: In the step S1, the mass concentration of the iridium precursor salt in the solution A is 0.001-0.005 g / mL, and the mass concentration of the ruthenium precursor salt is 0.001-0.003 g / mL.

6. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to claim 5, characterized in that: In step S1, the iridium precursor salt is selected from one or a combination of two or more of iridium trichloride, iridium tetrachloride, chloroiridic acid, iridium acetate, ammonium chloroiridate and potassium hexachloroiridate; the ruthenium precursor salt is selected from one or a combination of two or more of ruthenium trichloride, ruthenium tetrachloride, ruthenium acetylacetonate and ammonium hexachlororuthenate.

7. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to any one of claims 1 to 3, characterized in that: In the step S2, the concentration of the triblock copolymer P123 in the solution B is 0.1-1.0 mol / L.

8. The method for preparing a catalyst for proton exchange membrane hydrogen electrolysis according to claim 1, characterized in that: In step S4, the reaction temperature is 100-240° C., and the reaction time is 4-24 hours.

9. A catalyst for proton exchange membrane hydrogen electrolysis, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. The catalyst for proton exchange membrane hydrogen electrolysis according to claim 9, characterized in that: It is a core-shell structured nanoparticle with a size of 100~600nm.

Citation Information

Patent Citations

  • Preparation method of fuel cell PdIr alloy electrocatalyst

    CN115275234A

  • Preparation method of IrRu alloy catalyst

    CN116060630A

  • Preparation method and application of iridium-based electrocatalyst

    CN116083953A